Changing Trends and Prospects of Financial Technology - Alshanfari, Buthaina Marai; Alkaaf, Wafa; Khan, Mohammed Abdul Imran (New Innovations in Economics, Business and Management Vol. 7, 2022)
FinTech can completely transform the way financial services companies create, distribute, and monetize their products and services. This phrase could also be used to the technologies offered by these businesses. Fintech has made the most progress in the payments industry, whereas other industries have made less progress. Fintech has changed the financial environment in numerous ways. In addition to transactions, Fintech can be utilized to acquire financial advice. In the event of difficulty, NBFCs provide online support, allowing customers to contact a lender. Customers have embraced the concept of on-demand financing because of mobile and cloud technology. According to fintech trends, people are increasingly comfortable handling their money and business online, and they are less ready to put their money and business on the line. The chapter is a much-needed summary of the current trends and prospects of “Financial Technology” and its increasing importance. The chapter draws attention to the acceptance of fintech, its users and how it works; with a background showing history, advantages, disadvantages and its regulation. The chapter concludes with an analysis of fintech prospects.